Using EEG to explore how rTMS produces its effects on behavior - Johnson, Jeffrey S. (2009)
A commonly held view is that repetitive TMS (rTMS) influences behavior by producing transient “virtual lesions” in targeted tissue. However, findings of rTMS-related improvements in performance are difficult to reconcile with this assumption. With regard to the the mechanism of rTMS, a combined rTMS/EEG study conducted in our lab has revealed a complex set of relations between rTMS, EEG activity, and behavioral performance, with the effects of rTMS on power in the alpha band and on alpha:gamma phase synchrony each predicting its effect on behavior. These findings suggest that rTMS influences performance by biasing endogenous task-related oscillatory dynamics, rather than creating a “virtual lesion”. To further differentiate these two alternatives, in the present study we compared the effects of 10 Hz rTMS on neural activity with the results of an experiment in which rTMS was replaced with 10 Hz luminance flicker. We reasoned that 10 Hz flicker would produce widespread entrainment of neural activity to the flicker frequency, and comparison of these EEG results with those from the rTMS study would shed light on whether the latter also reflected entrainment to an exogenous stimulus. Results revealed pronounced evidence for “entrainment noise” produced by 10 Hz flicker – increased oscillatory power and inter-trial coherence (ITC) at the driving frequency, and increased alpha:gamma phase synchronization -- that were nonetheless largely uncorrelated with behavior. This contrasts markedly with 10-Hz rTMS, for which the only evidence for stimulation-induced noise, elevated ITC at 30 Hz, differed qualitatively from the flicker results. Simultaneous recording of the EEG thus offers an important means of directly testing assumptions about how rTMS exerts its effects on behavior.